PENGARUH ECONOMIC VALUE ADDED, MARKET VALUE ADDED, EARNINGS PER SHARE DAN FIRM SIZE TERHADAP RETURN SAHAM SYARIAH PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI ISSI - Dedi Irawan; Yudhistira Ardana (Jurnal Bisnis Darmajaya, 2018)
This study is intended to determine the effect of economic value added, market value added, earnings per share and firm size on Islamic stock returns on manufacturing companies listed in the Indonesian Syariah Stock Index in 2015-2017. This research will be analyzed using an error correction model commonly abbreviated as ECM. The sample in this study was obtained as many as 30 companies that joined the Indonesian Islamic Stock Index. Taken together the variables EVA, MVA, EPS and firm size have a significant effect on stock returns in both the short and long term indicated by the statistical F value of 0.041232 in the long term and short term of 0.00000 where the value is more small than α = 5% and the F value of statistics greater than the F table. Based on the data analysis that has been done, it can be seen that the EVA variables both long term and short term have no effect on stock returns.Keywords - Economic Value Added, Market Value Added, Earnings per Share, Firm Size to return